LANGUAGE INTERPRETATION CHALLENGES FOR EFL STUDENTS - Fikriani Aminun Omolu; A. Mappewali; Siti Aisyah Sundariyah; Dinda Aprilia Putri (Universitas Muhammadiyah Metro, 2022)
Despite many studies on this topic, it is a rare report that EFL students need help interpreting English to Bahasa or Bahasa to English. This study aims to reveal the challenges faced by students in interpreting and find the most appropriate solution to overcoming these challenges. The subject of this research is the fifth-semester students of the English Education Study Program of Universitas Muhammadiyah Palu. The instrument employs 10 statement items related to the difficulties that a novice interpreter might experience. The result shows that the students faced difficulties such as lack of vocabulary, terms translation, finding equivalent words, difficulty understanding pronunciation, mastery of the topic, remembering, limited time, anxiety, and concentration. While for the interpretation of numbers, the sample did not rate this as a difficulty. This study implies that teacher-educators to develop reading habits to overcome the lack of vocabulary by many models. Teacher-educators can use the original language, improve an equally good level of mastery in the source language and the target language, strengthen pronunciation skills, understand pre-condition in advance, take notes to face the memorization problem, broaden knowledge, have good preparation, realize the source of anxiety, mastering the topic to help reducing anxiety, having an excellent listening skill and self-control as the solution for concentration problem.